Medical Image Large Hemangiopericytoma of the Tongue - Suhail Amin Patigaroo; Zubair; Quratul Ain Batool (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2017)
These pictures are of a 45 -year old male patient with a swelling on the tip of tongue from the last one year. The swelling increased progressively in the last one year with a recent onset of mild discomfort. He has never shown to any physician before and once swelling reached to a large size he reported to us. MRI revealed a solid mass with isodense contrast in T1.